Long‐Term Student Benefit of International Agricultural Study Abroad Courses. Issue 1 (30th November 2017) - Butcher, Robert; Wiedenhoeft, Mary H.; Loynachan, Thomas E.
Abstract : Core Ideas: Do agricultural travel courses have an impact on the student‐travelers' careers, and do the employer and employee perceive any benefits? We surveyed 335 students who had participated in an Iowa State ag‐led international ag study course between 1964 and 1990. Overall the survey showed strong impacts and favorable attitudes decades after participation in an international agricultural travel course. Iowa State University College of Agriculture and Life Sciences (CALS) has offered international agricultural travel courses since 1963. Students traveled to Europe, Eastern Europe, or Asia on roughly a bi‐annual basis. We were interested in learning if agricultural travel courses had an impact on the student‐travelers' careers, and if the employer and employee perceived any benefits. Lists of student travelers collected over decades in the Agronomy Department at Iowa State University gave a unique opportunity to take a long‐term perspective. We sent 335 surveys to students who had participated in a CALS‐led international ag study course between 1964 and 1990. We received 132 valid responses. Respondents were asked to rate on a 5‐point Likert scale to what extent they agreed or disagreed with statements regarding their international study course and career advancement and their personal development and attitudes regarding international awareness and humanitarianism. The responses relating to significant career advancement correlated with overall positive attitudes, a mean of 3.70 on the 5‐point scale, toward the effect of student travel. Most respondents felt their employers benefitted as well. The questions on personal development such as improved self‐confidence had a mean score of 3.86, and broadened attitudes regarding others' customs and beliefs scored 4.22. One question regarding increased international interest had a mean score of 4.16. Overall the survey showed strong impacts and favorable attitudes decades after participation in an international agricultural travel course.